Structural and biophysical characterization of the type VII collagen vWFA2 subdomain leads to identification of two binding sites. Issue 4 (14th March 2020) - Gebauer, Jan M.; Flachsenberg, Florian; Windler, Cordula; Richer, Barbara; Baumann, Ulrich; Seeger, Karsten
Abstract : Type VII collagen is an extracellular matrix protein, which is important for skin stability; however, detailed information at the molecular level is scarce. The second vWFA (von Willebrand factor type A) domain of type VII collagen mediates important interactions, and immunization of mice induces skin blistering in certain strains. To understand vWFA2 function and the pathophysiological mechanisms leading to skin blistering, we structurally characterized this domain by X‐ray crystallography and NMR spectroscopy. Cell adhesion assays identified two new interactions: one with β1 integrin via its RGD motif and one with laminin‐332. The latter interaction was confirmed by surface plasmon resonance with a K D of about 1 mm . These data show that vWFA2 has additional functions in the extracellular matrix besides interacting with type I collagen. Abstract : Type VII collagen is an extracellular matrix protein, which is important for skin stability. The structure of the vWFA2 subdomain of type VII collagen has been determined, and it has been shown that vWFA2 interacts with integrins. In addition, a new interaction site for laminin‐332 was identified and characterized. These data provide new insights into vWFA2 functions in the extracellular matrix.